Murine astrocytes are responsive to the pro-inflammatory effects of IL-20. (24th August 2019) - Burmeister, Amanda R.; Johnson, M. Brittany; Marriott, Ian
Highlights: Primary murine and human astrocytes are not an appreciable source of IL-20 following bacterial challenge. Following administration of IL-20, primary astrocytes upregulated TLR and IL-1β expression, and IL-6 production. IL-20 acts in a dissimilar manner to other IL-10 family members to augment the inflammatory responses of astrocytes. Abstract: Glia are key regulators of inflammatory responses within the central nervous system (CNS) following infection or trauma. We have previously demonstrated the ability of activated astrocytes to rapidly produce pro-inflammatory mediators followed by a transition to an anti-inflammatory cytokine production profile that includes the immunosuppressive cytokine interleukin (IL)-10 and the closely related cytokines IL-19 and IL-24. IL-20, another member of the IL-10 family, is known to modulate immune cell activity in the periphery and we have previously demonstrated that astrocytes constitutively express the cognate receptors for this cytokine. However, the ability of glia to produce IL-20 remains unclear and the effects of this pleiotropic cytokine on glial immune functions have not been investigated. In this study, we report that primary murine and human astrocytes are not an appreciable source of IL-20 following challenge with disparate bacterial species or their components. Importantly, we have determined that astrocyte are responsive to the immunomodulatory actions of this cytokine by showing that recombinant IL-20 administration upregulates microbial pattern recognition receptor expression and induces release of the inflammatory mediator IL-6 by these cells. Taken together, these data suggest that IL-20 acts in a dissimilar manner to other IL-10 family members to augment the inflammatory responses of astrocytes.